2022
DOI: 10.3390/su14159057
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effect of Blue-Green Infrastructure on Microclimate and Human Thermal Comfort in Melbourne’s Central Business District

Abstract: Blue-green infrastructure (BGI) is defined as a strategically planned network of natural and semi-natural areas with other environmental features designed and managed to deliver a wide range of ecosystem services, which include microclimate regulation and enhanced human thermal comfort. While green infrastructure is widely known to be capable of mitigating the adverse effects of urban heat island, the effect of blue infrastructure to regulate thermal comfort is still poorly understood. This study investigates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 74 publications
2
4
0
Order By: Relevance
“…The implementation of multilayer planting design can increase the areas with higher relative humidity and moderate temperature. Existing studies have found advantages of increasing green coverage in regulating regional temperature and humidity [15,16]; this study focuses on intra-scale GSI [17] and the findings align with other regional-scale research. Meanwhile, including trees and shrubs can significantly improve the public perception of a rain garden from the perspectives of visual comfort, the landscape's visual beauty, and the overall favorite.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The implementation of multilayer planting design can increase the areas with higher relative humidity and moderate temperature. Existing studies have found advantages of increasing green coverage in regulating regional temperature and humidity [15,16]; this study focuses on intra-scale GSI [17] and the findings align with other regional-scale research. Meanwhile, including trees and shrubs can significantly improve the public perception of a rain garden from the perspectives of visual comfort, the landscape's visual beauty, and the overall favorite.…”
Section: Discussionsupporting
confidence: 66%
“…The microclimate of an area is decided by a combination of various environmental factors, such as temperature, solar radiation, humidity, wind, and air [15]. The microclimate is significantly shaped by the presence of specific elements in the site, such as buildings, vegetation, and construction materials [16]. Microclimate regulation is not solely affected by the regional green infrastructure system, intra-scale GSI design, such as green streets, vegetative swales, and rain gardens, can also control the microclimate and influence related spatial perceptions [17].…”
Section: Microclimate Impacts Of Gsi and The Urban Living Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the measured and simulated temperature and humidity data at a fixed location on Taiping Street during the hours of 10:00-20:00 on 12 July 2022, researchers found that the coefficient of determination (R 2 ) between the two sets of data was 0.91, the root mean square error (RMSE) was 1.68, and the index of agreement (d) was 0.75 for temperature, while the R 2 was 0.92, the RMSE was 3.2, and the d was 0.86 for humidity. Typically, an R 2 greater than 0.5 is considered reasonable (Santhi et al, 2001;Balany et al, 2022). The RMSE values for air temperature and relative humidity are within the range reported in many related studies (RMSE of relative humidity ranging from 2.04% to 11.12% and air temperature ranging from 0.52 °C to 4.30 °C) (Tsoka et al, 2018).…”
Section: Research Validationsupporting
confidence: 74%
“…The efficiency of different green infrastructures in attracting and promoting biodiversity is still restricted. With its ability to host and sustain urban wildlife, thus enhancing previously depauperate regions, green roofs, along with other urban green spaces, may have significant ecological value [54,55]. There is evidence that green roofs may boost cities' biological diversity if implemented widely [56,57].…”
Section: Introductionmentioning
confidence: 99%